The Potential Ecological Impact of Oil Palm Agroforestry as Term of Improvement for Restoring Harapan Rainforest - Rahmani, Tabah Arif; Nurrochmat, Dodik Ridho; Park, Mi Sun; Boer, Rizaldi; Ekayani, Meti (Institut Pertanian Bogor (IPB University), 2024)
Around 20.000 ha of forestland in the Harapan Rainforest, Jambi Province, Indonesia, is currently under encroachment by local communities. Local communities encroach on forest land converted into oil palm plantations. Expanding oil palm plantations into forest areas led to biodiversity loss and massive carbon emissions. The annual net carbon emissions of oil palm transformation from the forest in Indonesia is around 12.41–25.83 ton-1 ha-1 year-1. Oil palm agroforestry is considered to be able to increase carbon sequestration and the biodiversity level. CRC-990/EFForTS has established an oil palm agroforestry experimental plot in Jambi Province, Indonesia, namely B11 plot. This study compares the carbon sequestration and biodiversity level between oil palm monoculture and agroforestry. The data collected in this study was obtained from the CRC-990 experimental plots. We collected data on the CRC-990 oil palm agroforestry plot in 6 plots of 40 m × 40 m and 6 plots of 20 m × 20 m. We chose the location and theme of this research because, until now, no research has been conducted yet to calculate the potential carbon absorption capacity and biodiversity level of oil palm agroforestry patterns in B11 plot. This study uses an allometric equation and IPCC guidelines to estimate biomass and carbon sequestration. SNI 8014 is used to evaluate the biodiversity level. This study found that oil palm agroforestry has more significant carbon sequestration. Increasing intercropping in oil palm agroforestry will increase the amount of carbon sequestration. This study also found that oil palm agroforestry has a higher biodiversity level. The species diversity of oil palm agroforestry is moderate, while oil palm monoculture is low. These potential ecological impacts can be considered an initial step in restoring the Harapan Rainforest. It is important to choose appropriate intercrops and proper management to increase the successful implementation of oil palm agroforestry.